Comparative Study of Income of Sweet Potato Farmers' in Different Trade Channels in Bandorasa Wetan Village, Cilimus District, Kuningan Regency - Raja Intan Alam; Azzahra Maulida Mahira; Dwi Purnomo (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study aims to analyze the income of sweet potato farmers in Bandorasa Wetan Village, Kuningan Regency, by comparing different trading channels, specifically sales to middlemen and direct sales to the processing industry. Sweet potato farming plays a crucial role in supporting local and national economies, with Kuningan being a major sweet potato production area in West Java. Using a quantitative comparative approach with survey techniques, data was collected from 83 farmers, with 49 selling to middlemen and 34 to the industry. The results show that the average income of farmers selling to the industry (IDR 3,468,222) is significantly higher than those selling to middlemen (IDR 2,812,569), as evidenced by the independent sample test (p = 0.000). However, income from industry sales shows greater variability. This research contributes by highlighting the income disparities across trading channels, offering valuable insights for farmers and stakeholders in optimizing trading practices to maximize profitability. Future research should explore factors influencing channel selection, including market conditions and trading strategies, to enhance the overall sustainability and profitability of sweet potato farming.